Lactate Induces Pro-tumor Reprogramming in Intratumoral Plasmacytoid Dendritic Cells - Raychaudhuri, Deblina; Bhattacharya, Roopkatha; Sinha, Bishnu Prasad; Liu, Chinky Shiu Chen; Ghosh, Amrit Raj; Rahaman, Oindrila; Bandopadhyay, Purbita; Sarif, Jafar; D'Rozario, Ranit; Paul, Santu; Das, Anirban; Sarkar, Diptendra K.; et al. (Frontiers in Immunology, 2019)
Plasmacytoid dendritic cells are the most efficient producers of type I interferons, viz. IFNα, in the body and thus have the ability to influence anti-tumor immune responses. But repression of effective intra-tumoral pDC activation is a key immuno-evasion strategy exhibited in tumors ─ tumor-recruited pDCs are rendered “tolerogenic”, characterized by deficiency in IFNα induction and ability to expand regulatory T cells in situ. But the tumor-derived factors that drive this functional reprogramming of intra-tumoral pDCs are not established. In this study we aimed at exploring if intra-tumoral abundance of the oncometabolite lactate influences intra-tumoral pDC function. We found that lactate attenuates IFNα induction by pDCs mediated by intracellular Ca2+ mobilization triggered by cell surface GPR81 receptor as well as directly by cytosolic import of lactate in pDCs through the cell surface monocarboxylate transporters, affecting cellular metabolism needed for effective pDC activation. We also found that lactate enhances tryptophan metabolism and kynurenine production by pDCs which contribute to induction of FoxP3+ CD4+ regulatory T cells, the major immunosuppressive immune cell subset in tumor microenvironment. We validated these mechanisms of lactate-driven pDC reprogramming by looking into tumor recruited pDCs isolated from patients with breast cancers as well as in a preclinical model of breast cancer in mice. Thus we discovered a hitherto unknown link between intra-tumoral abundance of an oncometabolite resulting from metabolic adaptation in cancer cells and the pro-tumor tolerogenic function of tumor-recruited pDCs, revealing new therapeutic targets for potentiating anti-cancer immune responses.